X-Chromosome Inactivation is a Biomarker of Clinical Severity in Female Carriers of RPGR-Associated X-Linked Retinitis Pigmentosa - Fahim, Abigail T. (Ophthalmol Retina, 2019)
PURPOSE: X-linked retinitis pigmentosa can manifest in female carriers with widely variable severity, while others remain unaffected. The contribution of X-chromosome inactivation (XCI) to phenotypic variation has been postulated but not demonstrated. Furthermore, the impact of genotype and genetic modifiers has been demonstrated in affected males but has not been well established in female carriers. The purpose of this study is to describe the scope of clinical phenotype in female carriers with mutations in RPGR, and to quantify the contribution of genotype, genetic modifiers, and XCI to phenotypic severity. DESIGN: Cohort study. SUBJECTS: Seventy-seven female carriers with RPGR mutations from 41 pedigrees. METHODS: Coding single nucleotide polymorphisms were sequenced in candidate genetic modifier genes encoding known RPGR-interacting proteins. XCI ratios were determined in genomic DNA isolated from blood (n=42) and saliva (n=20) using methylation status of X-linked polymorphic repeats. These genetic data were compared to disease severity based on quantitative clinical parameters. MAIN OUTCOME MEASURES: Visual acuity (VA), Humphrey visual field (HVF), full field electroretinogram (ERG), and dark adaptation. RESULTS: Most individuals at all ages were mildly affected or unaffected, while the individuals who had progressed to moderate or severe vision loss were over the age of 30. RPGR genotype was not associated with clinical severity. The D1264N variant in RPGRIP1L was associated with more severe disease. Skewed XCI towards inactivation of the normal RPGR allele was associated with more severe disease. The XCI ratio in both blood and saliva was a predictor of visual function as measured by HVF diameter, rod amplitude, flicker amplitude, and flicker implicit time. For carriers with extreme XCI skewing of 80:20 or more, 57% were severely affected compared to 8% for this with XCI less than 80:20 (p=0.002). CONCLUSIONS: Female carriers with mutations in RPGR demonstrate widely variable clinical severity. XCI ratios correlate with clinical severity and may serve as a predictor of clinically significant disease. As RPGR gene therapy trials are underway, there will be a future imperative to determine which carriers require intervention and when to intervene. XCI analysis may be useful to identify candidates for early intervention.